IMPROVEMENT OF THE MECHANISM OF THE STATE SUPPORT OF DOMESTIC CINEMATOGRAPHY (ON THE EXAMPLE OF FRANCE) - M. Pankratova (Вестник университета)
In the article methods of state regulation are considered (economic, legal, administrative) film branches, the assessment and expediency of their application is given.